Characterization, pharmacokinetics, in vitro cytotoxicity of oxytetracycline-loaded CaCo₃ nanoparticle and its antibacterial and antibiofilm effects against Corynebacterium pseudotuberculosis isolated from goats - Banke, Idris Sherifat (2020)
Corynebacterium pseudotuberculosis is the causative agent of caseous lymphadenitis which is one of the most important bacterial diseases of goats causing significant economic losses with high prevalence worldwide. Currently, the treatment of the disease is via the administration of antibiotics combined with surgical excision, flushing and draining of the abscesses. This treatment protocol fails because the antibiotic does not get to the causative agent which is walled away in pus and excision further spreads the organism into the environment. For effective therapy, an improved method of drug delivery is therefore necessary. The main aim of the present study was to determine the effect of cockle shell derived calcium carbonate aragonite nanoparticle encapsulated oxytetracycline against Corynebacterium pseudotuberculosis isolated from goat caseous lymphadenitis. Calcium carbonate aragonite nanoparticle (CS-CaCO3NP) was synthesized from cockle shell using top down method and oxytetracycline (OTC) was loaded into it. Characterization to ensure that the CS-CaCO3NP and OTC-CS-CaCO3NP produced had the desired properties was done using Zeta analysis, transmission electron microscopy (TEM), field emission scanning electron microscopy (FESEM), X-ray diffraction (XRD), Fourier transform infra-red spectroscopy (FTIR) and Brunauer-emmett-teller (BET) surface area analysis. Then, the in vitro cytotoxicity evaluation of CS-CaCO3NP, OTC-CS-CaCO3NP and OTC was explored using MTT and Trypan blue assay in NIH3T3 cells. The antibacterial and antibiofilm effects of CS-CaCO3NP, OTC-CSCaCO3NP and OTC against C. pseudotuberculosis were also investigated using minimum inhibitory assay (MIC) and minimum biofilm eradication concentration (MBEC) assays. The antibacterial mode of action of OTC-CS-CaCO3NP on planktonic C. pseudotuberculosis was assessed using high resolution transmission electron microscopy (HR-TEM) while the antibiofilm effect was investigated using scanning electron (SEM) and fluorescent microscopy. Furthermore, for the pharmacokinetics study of OTC-CS-CaCO3NP and OTC, a total of 100, 5-6 weeks old female BALB/c mice divided into two groups of 50 mice each were used. They were administered 10mg/kg of OTC-CS-CaCO3NP and OTC, respectively. At specific time intervals of 0, 5, 10, 15, 30 minutes and 1, 2, 6, 24 and 48 hrs, five mice from each group were sacrificed. Blood, liver and kidneys were collected. The results revealed that the synthesized CS-CaCO3NP and OTC-CS-CaCO3NP had a homogeneously spherical appearance on TEM with a mean diameter of 29.90 (nm) and -19.9 (mV) zeta potential which increased to 62.40 nm and -23.5 (mV), respectively after loading with OTC. OTC crystallinity and functionality within CSCaCO3NP were maintained as showed by XRD and FTIR spectral peaks. The formulation of OTC-CS-CaCO3NP in ratio 1:4 with drug encapsulating efficiency (71%) was used for in vitro release study. OTC was sustainably released from OTCCS- CaCO3NP over a period of 96 hours with pH 4 having the highest drug release percentage (98.2%). Cytotoxicity assay revealed that OTC-CS-CaCO3NP had significantly higher cell viability (P < 0.05) compared to OTC in NIH3T3 cells. Loading OTC into CS-CaCO3NP reduced OTC cytotoxicity in NIH3T3 cells. MTT assay overestimated the cytotoxicity of CS-CaCO3NP, OTC-CS-CaCO3NP and OTC when compared to trypan blue assay. The minimum inhibitory concentration (MIC) for OTC-CS-CaCO3NP and OTC was 125 μg/ml and 500 μg/ml while the minimum biofilm eradication concentration (MBEC) was 250 μg/ml and >2000 μg/ml, respectively. However, CS-CaCO3NP alone demonstrated no antibacterial activity. HR-TEM revealed that the antimicrobial mechanism of action of OTC-CS-CaCO3NP was due to damage to the outer envelope of C. pseudotuberculosis while SEM and fluorescent microscope showed digestion and death of the bacteria cells within C. pseudotuberculosis biofilms. Pharmacokinetic studies demonstrated that OTC-CSCaCO3NP had a slower elimination rate (0.135 1/hr), longer half-life (5.133 hr), increased area under the curve (AUC) (46.68 μg/ml*h) and increased volume of distribution (1.587 mg/kg/μg/ml) than OTC. Thus, OTC-CS-CaCO3NP is a safe and biocompatible alternative antibiotic delivery system whose antibacterial efficacy is more pronounced compared to OTC.